Effects of Direct Contact Condensation on Flow Characteristics of Natural Circulation System at Low Pressure - Sun, Jianchuang; Ran, Xu; Zhang, Zhuohua; Cao, Xiaxin; Fan, Guangming; Ding, Ming (Frontiers in Energy Research, 2020)
Direct contact condensation (DCC) as a complex thermal-hydraulic phenomenon has been the subject of a great deal of research under forced flow conditions. It is an interesting challenge to study the phenomenon in a natural circulation system (NCS). In this paper, the flow behaviors along with DCC phenomena were experimentally investigated by a visualization method in an NCS at low pressure. Moreover, the influence of initial parameters including heat flux, inlet temperature and resistance of the heated section on the NCS was analyzed in detail. The experimental results revealed that two types of DCC phenomena were found in the NCS. When Type I DCC occurs, the interface wave will be formed due to the hydraulic jump caused by the reverse flow of subcooled water. The interface wave easily contributes to the occurrence of Type II DCC due to the Kelvin-Helmholtz instability. In addition, the NCS tends to be more unstable with the increase in the heat flux or the inlet resistance. The influence of inlet temperature on the flow rate should comprehensively consider the changes of outlet parameters and subcooled degree of the steam and the subcooled water.